Metodologías activas en la enseñanza-aprendizaje de lengua y literatura de los estudiantes del subnivel medio de la escuela “Sebastián de Benalcázar” parroquia las mercedes, cantón las naves, periodo lectivo 2021-2022 - Murillo Malagón , Irene Dalila (2022)
The main objective of this study was to analyze the active methodologies and their incidence in the teaching-learning of Language and Literature of the students of the Middle Sublevel of the "Sebastián de Benalcázar" School, Parish of Las Mercedes, Canton Las Naves, Province of Bolívar, during the school year 2021-2022. The methodology applied for the research was qualitative, quantitative, bibliographic and field, the methods used were inductive and deductive, among the techniques used for the collection of information were observation, interview with the director and a survey applied to 7 teachers of the institution and 66 students of the middle sub-level (fifth, sixth and seventh grade of elementary school). As a proposal for improvement, a teacher training plan was developed on active methodologies for the improvement of teaching and learning of Language and Literature, which allowed for the training of 7 teachers and a director. It was concluded that active methodologies propose the construction of meaningful learning, where students become active actors in the teaching-learning process, allowing them to create, formulate new ideas, contribute with creative solutions, demonstrate skills and cognitive competencies and develop new capabilities that contribute to their training process. It is recommended to put into practice the training approached since these new forms of teaching promote in students a self-critical and reflective formation.